If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7q + q + -8q + 2q + -2 = 18 Reorder the terms: -2 + 7q + q + -8q + 2q = 18 Combine like terms: 7q + q = 8q -2 + 8q + -8q + 2q = 18 Combine like terms: 8q + -8q = 0 -2 + 0 + 2q = 18 -2 + 2q = 18 Solving -2 + 2q = 18 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2q = 18 + 2 Combine like terms: -2 + 2 = 0 0 + 2q = 18 + 2 2q = 18 + 2 Combine like terms: 18 + 2 = 20 2q = 20 Divide each side by '2'. q = 10 Simplifying q = 10
| x+2(x-2)=60 | | 4x+x-3=93 | | 15+35=-5(3x-10) | | 30-10x=5(2p-6) | | a^3-5a^2-16a+80=0 | | 45*2y=45 | | 4(6+3.2w)+7=60.2 | | 2(1)+1-3(1)+4= | | -12t+12t+-t+-11=3 | | 5(p-8)=-36+5p | | A(n)=2+(4-1)(-2.5) | | X+2x+x=32 | | 2(3x+6)=-36+30 | | h-h+h=7 | | 4t-t=18 | | 8(x-0.25)=4(2x-0.5) | | 5/34*17/20= | | 2q-5q+-9q=12 | | 5x-3=93 | | 0.20x+0.45(30)=25.5 | | 8-(3n-6)=9-4n | | (x-2)(x+1)=3 | | 11-2x=5(x+1)-7x | | t^6+6t^3-27=0 | | 9r+3=37r+7 | | 3(3+c)=2(c-7) | | k-2k+-7k=-18 | | 5x+21+3x=29 | | 10-2r=28 | | 3(n+1)-(7n-5)=-5n | | 2.33=(x-78)/3 | | 4+8=6+g |